2019
DOI: 10.3390/su11143824
|View full text |Cite
|
Sign up to set email alerts
|

Recycling Agricultural Wastes and By-products in Organic Farming: Biofertilizer Production, Yield Performance and Carbon Footprint Analysis

Abstract: The Circular Economy concept implies the re-design of existing production systems in agriculture, by promoting agricultural waste recycling. In an organic zucchini—lettuce rotation, two different agroecological tools were considered: biofertilizer and presence or absence of green manure (GM+ and GM−). In particular, we compared: (i) anaerobic digestate from cattle manure, co-composted with vegetable wastes, with the presence of GM (AD GM+); (ii) olive pomace compost, re-composted, with the presence of GM (OWC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(69 citation statements)
references
References 51 publications
2
50
0
3
Order By: Relevance
“…Globally, total organic solid wastes produced from livestock, human, and crop activities are more than 38 billion m 3 [6]. Rice straw produced in bulk quantity and poor feed for animals having higher silica and lingo-cellulose contents; is rather difficult to manage or dispose of [7].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, total organic solid wastes produced from livestock, human, and crop activities are more than 38 billion m 3 [6]. Rice straw produced in bulk quantity and poor feed for animals having higher silica and lingo-cellulose contents; is rather difficult to manage or dispose of [7].…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2019, 9, 4148 2 of 15 of agro-ecological service crops (ASC; [4]), utilization of soil amendments [5], and crop/livestock mixing can increase agro-ecosystem diversity and complexity both over space and time [6].A prerequisite to the systems sustainability implementation is the development, improvement, and/or choice of the best possible assessment methods. In fact, there is a need to determine the reliability of innovative management practices with respect to the conventional ones, and to clarify the benefits and the drawbacks of the full or partial application of an agro-ecological approach.…”
mentioning
confidence: 99%
“…Sci. 2019, 9, 4148 2 of 15 of agro-ecological service crops (ASC; [4]), utilization of soil amendments [5], and crop/livestock mixing can increase agro-ecosystem diversity and complexity both over space and time [6].…”
mentioning
confidence: 99%
“…Referring only to global warming, in our experimental conditions the production of 1 ton of LC caused an emission of 250 kg of CO 2 eq; while the production of 1 ton of HC caused an emission of 199 kg of CO 2 eq. Diacono et al 2019 [70], using anaerobic digestate from cattle manure, reported a cumulative emission of about 31.4 kg CO 2 eq ton −1 under an aerated composting process. This value is lower if compared to ours due mostly to the raw materials used in the different studies (particularly, low dry matter content of green waste utilized in this study).…”
Section: Environmental Aspectsmentioning
confidence: 99%